(untitled) - Minogue, K. R. (London, 1963)
The Liberal Mind attempts to uncover the philosophy of liberalism and lay bare its implications. What is Man? How does he think and feel? What is the place of Reason in human affairs? How should men live? What is politics, and what is it for? Kenneth Minogue offers a brilliant and provocative exploration of liberalism in the Western world today: its roots and its influences, its present state, and its prospects in the new century. While few - especially in America - embrace the description of liberal, Minogue argues, most Americans and most Europeans behave as liberals. At least they are the heirs of what Minogue describes as "the triumph of an enlarged, flexible, and pragmatic version of liberalism." The past two centuries have been characterised, in the West at least, by "the fury of old ideological battles...such as: A planned economy, or free enterprise? Individual thrift, or social services? Free trade, or protection?" These battles have largely been completed - and, many would say, have been won by the champions of, respectively, free enterprise, individual thrift, and free trade.
Keywords: Liberalism